Pengaruh Struktur.Modal, Operating Leverage, Financial Leverage, Dan Likuiditas.Terhadap Risiko Investasi Saham Pada Perusahaan Sub Sektor Restoran, Hotel Dan Pariwisata Di Bei Periode 2017-2019 - Ida Ayu Pradnya Sari; Gede Aryawan; A.A.A Erna Trisna Dewi (Jurnal Riset Akuntansi Warmadewa, 2021)
This study is entitled The Influence of Capital Structure, Operating Leverage, Financial Leverage and Liquidity on Stock Investment Risk in Sub-Sector Companies, Restaurants, Hotels, and Tourism on the IDX 2017-2019 Period. The risk of stock investment will never occur if economic principles remain in line, meaning that every market participant makes sacrifices that are as minimal as they can to get maximum usage. Research on investment risk and the factors that influence it is very important to do so that it will help investors and make decisions to invest. This study aims to determine partially the structure, capital, operating leverage, financial leverage, and liquidity of the risk of stock investment in restaurant, hotel and tourism sub-sector companies on the Indonesia Stock Exchange (BEI) 2017-2019 period. The sampling technique used was purposive sampling and obtained a total sample of 16 companies that had met the criteria with a total of 35 selected companies. Based on the data sources used in this research, all of them are secondary data, namely by accessing the Indonesia Stock Exchange Website. The data analysis technique used in this study is multiple linear regression analysis. Capital structure has a positive effect on stock investment risk, Operating leverage has no effect on investment risk, stocks, financial leverage has a positive effect on investment risk, shares and liquidity has a positive effect on the risk of stock investment in companies in the sub-sector, hotels, hotels , and tourism on the Indonesia Stock Exchange.